Proceedings of the 2020 ACM Conference on Innovation and Technology in Computer Science Education 2020
DOI: 10.1145/3341525.3387404
|View full text |Cite
|
Sign up to set email alerts
|

Engage Against the Machine: Rise of the Notional Machines as Effective Pedagogical Devices

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…There exist numerous strategies to help learners acquire this abstract understanding. One strategy is to explicitly teach a notional machine , ,, i.e., an abstract model of the program execution environment. Another strategy is to teach using many relevant examples, each showing different representations of the same concepts. , Exposure to many representations or orientations of the same concept can help students perceive the abstract principles that underlie the surface-level characteristics of any single example.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There exist numerous strategies to help learners acquire this abstract understanding. One strategy is to explicitly teach a notional machine , ,, i.e., an abstract model of the program execution environment. Another strategy is to teach using many relevant examples, each showing different representations of the same concepts. , Exposure to many representations or orientations of the same concept can help students perceive the abstract principles that underlie the surface-level characteristics of any single example.…”
Section: Discussionmentioning
confidence: 99%
“…Every programming course involves a notional machine, either implicitly in the programming language and features used or explicitly taught by the instructor. 28 It has been argued that notional machines ought to be explicitly taught in introductory programming courses (e.g., Sorva, 28 Dickson et al 30 ).…”
Section: Mental Models and Notional Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayman and Mayer [1988] first showed that an appropriate conceptual model for BASIC could help students "develop fewer misconceptions [...] and perform better on transfer tests. " du Boulay [1986] coined the term "notional machine" for conceptual models specifically of a language's dynamic semantics, which has received renewed focus in recent years [Dickson et al 2020]. Our work differs from most research on notional machines by focusing equally on a conceptual model of static semantics.…”
Section: Related Workmentioning
confidence: 99%
“…These tools range from automated assessment systems (for reviews, see e.g. [15]- [18]) and systems used to illustrate how programs work [19], [20]. While automated assessment systems originally focused on functional correctness of programs (cf.…”
Section: Background a Automated Assessment And Feedback In Programmingmentioning
confidence: 99%